Esketamine new tool for resistant depressive disorder. About a case - M. Valverde Barea; C. Mata Castro; P. Vargas Melero; A. España Osuna (European Psychiatry, 2024)
Introduction Depressive disorders represent the main cause of disability in the world, due to its prevalence, its impact on the patient’s quality of life and its role as one of the main risk factors for suicide. Current antidepressant treatments can take weeks to take effect and months to achieve response and remission.It is estimated that up to 30% of patients with major depressive disorder (MDD) are resistant to antidepressant treatment, in addition, approximately 30-45% of patients with depression do not achieve an adequate response to the first antidepressant treatment.According to the STAR*D study, the more lines of treatment are required, the lower remission rates are estimated, as well as higher relapse rates during the follow-up phase.With the appearance of intranasal dosage esketamine allows the release directly to the central nervous system, the mechanism of action of esketamine is based on the antagonism of the NMDA receptor, which entails the modulation of the excitatory transmission of glutamate and the release of BDNF,activating neurotrophic signaling and synaptogenesis.